The Synergy of Artificial Intelligence and Emotional Intelligence in Human Resource Development: A Systematic Literature Review of Digital-Era Organizational Transformation - Syukron Afandi; Mohammad Fakhruddin Mudzakkir (LPPM Institut Pendidikan Nusantara Global, 2026)
This systematic literature review examines how Artificial Intelligence (AI) and Emotional Intelligence (EI) jointly shape Human Resource Development (HRD) in the digital era. Following PRISMA guidelines, we searched Scopus for peer-reviewed English-language journal articles and conference proceedings published between 2019 and January 2026 addressing AI, EI, and HRD/HRM. From 81 records, 14 studies met the inclusion criteria and were analyzed using thematic synthesis. Five themes emerged: (1) AI-driven HRD decision-making, (2) EI as a critical digital-era competency, (3) human–AI collaboration mechanisms, (4) ethical challenges including algorithmic bias and workplace dehumanization, and (5) emerging theoretical frameworks. Unlike prior studies that frame AI as substitutive, our findings advance a human–AI collaboration perspective, demonstrating that AI and EI operate as complementary capabilities. AI strengthens efficiency, scalability, and predictive accuracy, while EI provides contextual judgment, ethical oversight, empathy, and trust-building. In AI-driven recruitment, managerial EI is crucial for identifying and correcting algorithmic bias and for ensuring fair, transparent decision-making. Drawing on Socio-Technical Systems Theory, we argue that digital transformation requires joint optimization of technological systems (AI) and social capabilities (EI). We propose the AI–EI Synergy Framework (AIEIS-HRD), outlining four integration mechanisms: complementarity, augmentation, moderation, and mediation. Sustainable HRD transformation depends on balancing technological advancement with emotionally intelligent governance.